(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, the dependence of bronchoobstructive syndrome (BOS)on reflux environment 86 patients with gastroesophageal reflux disease (GERD) was studied. The results of the investigation showed that the origin of BOS in GERD and the degree of development of clinical symptoms depending on the background of reflux were compared with reflux environment and the following were found: Heartburn is observed in patients with BOS, in whom. BOS appears with a bitter taste in the mouth in the advanced state. Clinical signs are determined in diagnosis and treatment according to different (acidic, alkaline) requirements in GERD patients.